Well Pattern and Well Spacing Optimization of Large Volume Water Injection in a Low-Permeability Reservoir with Pressure Sensitivity. (19th August 2022) - Zhan, Jie; Tian, Yafei; Fan, Chao; Ma, Xianlin; Nie, Ren-Shi; Ji, Dongqi; Li, Teng; Yu, Hongyan
Abstract : Even with the fractured wells, the primary oil recovery of low-permeability reservoirs is still poor in Block X of Shengli Oilfield. To further enhance the oil recovery, water is injected into the reservoir. Different from the conventional injection scheme, the maximum daily injection rate of the proposed scheme by Shengli Oilfield reaches 2000 m 3, and the average daily injection rate is around 1500 m 3 . Thus, the conventional well spacing of certain well pattern is not suitable for the novel injection scheme. In the paper, the optimal well pattern and well spacing for the large volume water injection scheme to develop a pressure-sensitive low-permeability reservoir is investigated. Firstly, the CMG is employed to build the basic reservoir model developed by fractured vertical wells. To finely depict the pressure sensitivity, the dilation-recompaction geomechanical model is introduced to couple with the basic reservoir model. Based on the established coupled model, the optimal well spacing for the inverted 5-spot well pattern and the inverted 9-spot well pattern is investigated with a total of 80 sets of numerical experiments. The numerical experiments indicate that the optimal well spacing for the inverted 5-spot well pattern is 850 m/350 m and the optimal well spacing for the inverted 9-spot well pattern is 550 m/450 m. To further screen the well pattern, the normalized index of oil production per unit area of each well pattern is proposed. And it is found that the oil production per unit area of the inverted 5-spot well pattern is higher than the inverted 9-spot well pattern. For the reservoir developed with fractured vertical wells coupled with large volume water injection, compared with the inverted 9-spot well pattern, the inverted 5-spot well pattern is better, and the corresponding optimal well spacing is 850 m/350 m. The paper proposes an efficient simulation and optimization workflow for the development of pressure-sensitive low-permeability reservoirs with fractured vertical wells coupled with large volume water injection, providing practical guidance for the efficient and sustainable development of pressure-sensitive low-permeability reservoirs.